Response to the comment regarding the article “The Pain Ratio Before and After the Application of Physiotherapy for Dysfunction of the Temporomandibular Joint” (Journal of Health Sciences, 2025)
Dear editor,We would like to express our sincere gratitude for the attention given to our published scientific paper, as well as for the positive comments, valuable suggestions, and thoughtful questions in the Comment on the article by Bajpai. We consider his contribution extremely important for improving the quality of future research in this field.